2011
DOI: 10.1016/j.canlet.2010.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 induces apoptosis and paraptosis-like cell death in colorectal cancer cells through activation of p53

Abstract: Ginsenosides are the main bioactive components in American ginseng, a commonly used herb. In this study, we showed that the ginsenoside Rh2 exhibited significantly more potent cell death activity than the ginsenoside Rg3 in HCT116 and SW480 colorectal cancer cells. Cell death induced by Rh2 is mediated in part by the caspase-dependent apoptosis and in part by the caspaseindependent paraptosis, a type of cell death that is characterized by the accumulation of cytoplasmic vacuoles. Treatment of cells with Rh2 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
159
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(166 citation statements)
references
References 23 publications
5
159
2
Order By: Relevance
“…[25][26][27][28] Moreover, GRh2 can kill colorectal cancer cells and its cytotoxic effect is significantly more potent than GRg3. 29) Our findings are consistent with these previous reports: As shown in Fig. 2, 20(S)-GRh2 had a more potent toxic effect on Reh cells with an IC 50 value of around 40 µM than GRg3 with an IC 50 value of around 100 µM.…”
Section: Discussionsupporting
confidence: 93%
“…[25][26][27][28] Moreover, GRh2 can kill colorectal cancer cells and its cytotoxic effect is significantly more potent than GRg3. 29) Our findings are consistent with these previous reports: As shown in Fig. 2, 20(S)-GRh2 had a more potent toxic effect on Reh cells with an IC 50 value of around 40 µM than GRg3 with an IC 50 value of around 100 µM.…”
Section: Discussionsupporting
confidence: 93%
“…Otherwise, p53 and the p53-responsive gene, p21, can suppress cyclin B1 and cdc2 expression by inhibiting either cdc2 kinase activity or blocking the interaction of cyclin B1-cdc2 complexes with their substrates, leading to G2/M-phase cell cycle arrest (23)(24)(25)(26)(27). Furthermore, the MEK-ERK pathway has crosstalk with p53/p21, and Bax is a key target of the p53 transcription process in aspects of cell apoptosis (26). In the case of our study, the data showed that DADS downregulated cyclin B1, cdc2, p-cdc2 and cdc25c expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Then, ERK1/2 activation leads to phosphorylation of a variety of transcription factors and results in proliferation and differentiation, protecting cells against apoptosis (29). MEK-ERK signaling cascade may be affected by the activation of the p53/p21 pathway (26). Although DADS was reported to rapidly and potently inhibit the phosphorylation of ERK1/2 to induce apoptosis in human leukemia cell line HL-60 (21), other studies showed that DADS activated ERK1/2 in human non-small cell lung carcinoma H1299 cell death (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several health benefits of Rh2 have been reported due to its anti-inflammatory, antiGinsenoside Rh2 mediates changes in the microRNA expression profile of human non-small cell lung cancer A549 cells osteoclastogenic, anti-hyperglycemic and anticancer effects (10)(11)(12)(13)(14). The anticancer effect of Rh2 has been particularly observed in NSCLCs.…”
Section: Introductionmentioning
confidence: 99%